ANALYSIS THE EFFECT OF POLYSEMY ON THE SPEECH LEARNING FROM COVID-19 BY NADIEM MAKARIM TO ELEMENTARY STUDENT - Wahyuni, Resty; Siregar, Alfitriani; Agustriani, Habibah Eka (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
This study entitled œAnalysis the Effect of Polysemy on the Speech Learning from Covid-19 by Nadiem Makarim to Elementary School Student. The objectives of this study were (1) to identify the types of polysemy, (2) to investigate polysemy elements used in the speech, and (3) to identify the effect of polysemy were used on the speech to elementary students. The descriptive qualitative is applied in this study. The data were obtained from the speech by Nadiem makarim using documentation method. Afterward, analysis of this study use data reduction, data display, conclusion drawing and verification. The findings of the research show that there are 65 data of polysemy™s words which find in Learning from Covid-19 speech. Based on the types of polysemy, most of Irregular Polysemy were 38 words (58.5%) and followed by Regular Polysemy with 27 words (41.5%). The effect of polysemy on the speech to the elementary student has not been widely applied to elementary school students. Inasmuch as, the student has limited complex reasoning to a word that has another meaning and is critical. In a sentence, polysemy plays an important role and has the function to distinguish the meaning of a word meaning.